Stakeholder Ownership in Evaluating a Qur'an Memorization Program: an Empowerment Evaluation Study - Nazikhah, Ridha Khusnun; Suwadi (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
This study analyzes how stakeholder ownership is formed, distributed, and limited in the evaluation of a Qur'an memorization program at Madrasah Ibtidaiyah Al-Islamiyah Grojogan, Bantul, Indonesia. Although tahfidz programs are increasingly used to strengthen Qur'anic literacy and religious character in Islamic elementary schools, their evaluation is often limited to memorization targets, administrative reports, and student assessment results. Using a qualitative case study design and an empowerment evaluation perspective, this study involved nine stakeholders consisting of a tahfidz coordinator, tahfidz teachers, parents, and students. Data were collected through semi-structured interviews, observation of memorization activities and evaluation meetings, and analysis of memorization records, progress reports, and coordination notes. Data were analyzed using Miles, Huberman, and Saldana's interactive model and coded through the stages of establishing a mission, taking stock, and capacity building, combined with ownership indicators: choice, voice, control, responsibility, and emotional attachment. The findings show that ownership emerged in a hierarchical pattern. The coordinator and teachers demonstrated strong ownership because they had access to goals, data, reflection, and follow-up decisions. Parents and students supported the program emotionally and practically, but their evaluative voice and control remained limited. The study contributes to Islamic education evaluation by showing that empowerment evaluation can strengthen ownership when participation is supported by evaluation literacy, child-friendly reflection, and clear mechanisms for shared follow-up action.